(p+2q)(2p-q)-(p+q)(p-q)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 20:22:24
(p+2q)(2p-q)-(p+q)(p-q)(p+2q)(2p-q)-(p+q)(p-q)(p+2q)(2p-q)-(p+q)(p-q)=(2p²-pq+4pq-2q²)-(p&
(p+2q)(2p-q)-(p+q)(p-q)
(p+2q)(2p-q)-(p+q)(p-q)
(p+2q)(2p-q)-(p+q)(p-q)
=(2p²-pq+4pq-2q²)-(p²-q²)
=p²+3pq-q²
(p+2q)(2p-q)-(p+q)(p-q)
(p-q)^4/(q-p)^3*(p-q)^2 计算
计算:(p-q)^2 * (p-q)^3 * (q-p)^5
(p-q)^5/(q-p)^2·(p-q)^3
m^2(p-q)-P+q
6(p+q)^2-12(p+q)
(p-2q)^2-2(p+2q)(p+3q)+(p+3q)^2
因式分解(p+2q)^2-2(p+2q)(p+3q)+(p+3q)^2
(m-n)(p-q)(p+2q)-(n-m)(p+q)(p+2q)
6(p-q)^2-12(q+p) =6(p+q)(p-q) -12(p+q) =6(p+q) (p-q-2)
p-[q+2p-( )]=3p-2q
p(p+q)2-(p-q)(p2+pq+q2)
因式分解(p+2q)^2-2(p+2q)(p+3q)+(p+3q)(3q-p)
p.q.
因式分解(2p+q)(8p-3q)-2p(2p+q)
先化简再求值:(p+2q)^2-2(p+2q)(p+3q)+(p+2q)(3q-p),其中p=-1,q=-2
将[(p-q)³-2(q-p)²-2/3(q-p)]/ p-q/3(p≠q)化归为关于p、q的多项式
4(2p+3q)^2 -(3p-q)^2